Sinergi Literasi Keuangan dan Fintech: Meningkatkan Kinerja UMKM melalui Inklusi Keuangan - Munasib, Najat; Fitriyah, Fitriyah (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The purpose of this study is to examine the effect of Financial Literacy and Financial Technology (Fintech) on the performance of MSMEs with Financial Inclusion as a mediator. Methodology/approach: The research method used  in this study was quantitative and descriptive analysis. The sampling technique was carried out by distributing questionnaires to micro, small, and medium enterprises (MSMEs). The test tool used in this study was Partial Least Squares (PLS) with a sample size of one hundred and ten respondents. Results/findings: The results of the study indicate that Financial Literacy and Financial Technology have no effect on MSME performance. Financial inclusion affects MSME Performance. Financial Inclusion does not serve as a mediating variable in the relationship between financial literacy and MSME performance. Financial Inclusion mediates the influence of Financial Technology on MSME performance. Conclusions: Although financial technology aims to facilitate financial transactions, the low understanding of this technology can actually be an obstacle for business actors. Thus, the level of financial literacy and understanding of technology are important factors in optimizing the role of financial technology in driving MSME performance. Limitations: This study was only carried out on micro, small, and medium enterprises (MSMEs) in Lowokwaru District, Malang City, with predetermined criteria. Contribution: This study can be used as a consideration and reference related to decision making for the progress of growth in culinary Micro, Small and Medium Enterprises (MSMEs) in Malang City.